Evaluation of the protective role of ellagic acid in retinal degeneration: an experimental model - Eman E. Mousa; Aziza A. Elsaied; Mohammad M. Murad; Amal E. Ibrahim (Journal of the Arab Society for Medical Research)
Background/aim Ellagic acid (EA) is widely recognized as a natural compound with pharmacological potency as a polyphenolic molecule, possessing antioxidant, anti-inflammatory, antimutagenic, and antiproliferative characteristics. The present study aims to evaluate the potential neuroprotective effect of EA in retinal degeneration induced experimentally in rabbits. Material and methods A total of 27 male white New Zealand rabbits, with an average weight ranging from 1.5 to 2 kg, were divided into three groups (nine each). Group I served as the control group, while group II and group III, the macular degeneration (MD) induction groups that received a single intravitreal injection of sodium iodate (SI). Following the injection, group III was given 50 mg/kg of EA powder for 21 days, starting immediately after MD induction. Ophthalmic examinations of the retinas were conducted on days 7, 14, and 21 using a fundus camera, followed by electroretinogram (ERG) recording after MD induction. Apoptotic caspase-3 and caspase-7 activities in the retina tissues were also measured postdecapitation. Results The results showed a significant decrease (P≤0.05) in electroretinogram ‘a- and b-waves’ following intravitreal SI injection in group II and III comparing with control group. The pattern of internucleosomal fragmentation, indicating apoptosis, was time-dependent. The injection also increased relative caspase-3 and caspase-7 activity. However, group III of rabbits that is treated with EA exhibited noticeable improvements in these outcomes in comparing with group of MD-induced rabbits. Conclusions The administration of EA demonstrated a notable impact in improving the retina’s function, and decreased the apoptosis levels in MD model of rabbits